PcsR2 Is a LuxR-Type Regulator That Is Upregulated on Wheat Roots and Is Unique to Pseudomonas chlororaphis - Pan, Huiqiao; Pierson, Leland S.; Pierson, Elizabeth A. (Frontiers in Microbiology, 2020)
LuxR solos are common in plant-associated bacteria and increasingly recognized for playing important roles in plant-microbe interkingdom signaling. Unlike the LuxR-type transcriptional regulators of prototype LuxR/LuxI quorum sensing systems, LuxR solos do not have a LuxI-type autoinducer synthase associated with them. LuxR solos in plant-pathogenic bacteria play important roles in virulence and in plant-beneficial bacteria contribute to symbiosis. In the present study, we identified a LuxR solo, PcsR2, in the biological control species Pseudomonas chlororaphis 30-84. Unlike the LuxR solos in most of the plant-associated bacteria characterized to date, PcsR2 is not associated with a proline iminopeptidase gene and the protein has an atypical N-terminal binding domain. Moreover, it is highly conserved among P. chlororaphis species. Quantitative RT-PCR showed that the expression of pcsR2 was upregulated nearly 10-fold when this strain was grown on wheat roots. Using a GFP transcriptional reporter, we found that pcsR2 responded specifically to root-derived substrates as compared to leaf-derived substrates and did not respond to endogenously produced AHLs. We created a pcsR2 deletion mutant and found it was impaired in the ability to utilize root carbon and nitrogen sources in wheat root macerate and to colonize wheat roots. Phenazine production and most biofilm traits previously shown to be correlated with phenazine production also were diminished in the mutant. We determined that the gene expression of several of the proteins in the phenazine regulatory network including PhzR, Pip (phenazine inducing protein) and RpeA/RpeB were reduced in the mutant, and that overexpression of these genes in trans could restore phenazine production in the mutant to wild-type levels, indicating PcsR2 acts upstream of these regulatory genes. Our results indicate PcsR2 is a member of a novel subfamily of LuxR-family transcriptional regulators that regulates gene expression in response to unknown plant signals and is highly conserved among P. chlororaphis species.